Technical Note: System for evaluating local hypothermia as a radioprotector of the rectum in a small animal model. Issue 8 (16th June 2017) - Hrycushko, Brian A.; Bing, Chenchen; Futch, Cecil; Wodzak, Michelle; Stojadinovic, Strahinja; Medin, Paul M.; Chopra, Rajiv
Abstract : Purpose: The protective effects of induced or even accidental hypothermia on the human body are widespread with several medical uses currently under active research. In vitro experiments using human cell lines have shown hypothermia provides a radioprotective effect that becomes more pronounced at large, single‐fraction doses common to stereotactic body radiotherapy (SBRT) and stereotactic radiosurgery (SRS) treatments. This work describes the development of a system to evaluate local hypothermia for a radioprotective effect of the rat rectum during a large dose of radiation relevant to prostate SBRT. This includes the evaluation of a 3D‐printed small animal rectal cooling device and the integration with a small animal irradiator. Methods: A 3‐cm long, dual‐lumen rectal temperature control apparatus (RTCA) was designed in SOLIDWORKS CAD for 3D printing. The RTCA was capable of recirculating flow in a device small enough for insertion into the rat rectum, with a metal support rod for strength as well as visibility during radiation treatment planning. The outer walls of the RTCA comprised of thin heat shrink plastic, achieving efficient heat transfer into adjacent tissues. Following leak‐proof testing, fiber optic temperature probes were used to evaluate the temperature over time when placed adjacent to the cooling device within the rat rectum. MRI thermometry characterized the relative temperature distribution in concentric ROIs surrounding the probe. Integration with an image‐guided small animal irradiator and associated treatment planning system included evaluation for imaging artifacts and effect of brass tubing on dose calculation. Results: The rectal temperature adjacent to the cooling device decreased from body temperature to 15°C within 10–20 min from device insertion and was maintained at 15 ± 3°C during active cooling for the evaluated time of one hour. MR thermometry revealed a steep temperature gradient with increasing distance from the cooling device with the desired temperature range maintained within the surrounding few millimeters. Conclusions: A 3D‐printed rectal cooling device was fabricated for the purpose of inducing local hypothermia in the rat rectum. The RTCA was simply integrated with an image‐guided small animal irradiator and Monte Carlo‐based treatment planning system to facilitate an in vivo investigation of the radioprotective effect of hypothermia for late rectal toxicity following a single large dose of radiation.